REMOVAL OF AN ACID DYE FROM AQUEOUS SOLUTIONS BY ADSORPTION ON A COMMERCIAL GRANULAR ACTIVATED CARBON: EQUILIBRIUM, KINETIC AND THERMODYNAMIC STUDY - Marius Sebastian Secula; Benoît Cagnon; Igor Creţescu; Mariana Diaconu; Stelian Petrescu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The present paper approaches the study of the adsorption of an acid dye on a commercial granular activated carbon (GAC). Batch experiments were conducted to study the equilibrium isotherms and kinetics of Indigo Carmine on GAC. The kinetic data were analyzed using the Lagargren, Ho, Elovich, Weber-Morris and Bangham models in order to establish the most adequate model that describes this process, and to investigate the rate of IC adsorption. Equilibrium data were fitted to Langmuir and Freundlich isotherms. Langmuir isotherm equilibrium model and Ho kinetic model fitted best the experimental data.The effects of temperature (25 – 45 °C), initial concentration of dye (7.5 – 150 mg•L−1), GAC dose (0.02 – 1 g•L-1), particle size (2 – 7 mm in diameter), solution pH (3 – 11) on GAC adsorption capacity were established. The adsorption process is found to be favored by a neutral pH, high values of temperature and small particle sizes. The highest adsorption capacity (133.8 mg•g-1) of the GAC is obtained at 45 °C. The removal efficiency increases with GAC dose at relatively low initial concentrations of dye. Thermodynamic parameters such as standard enthalpy (H), standard entropy (S) and standard free energy (G) were evaluated. The adsorption of Indigo Carmine onto GAC is an endothermic process.